Economic recession and dimensions of poverty in Lafia: Some reflections since May, 2015 - Ukomi, Macaulay Peter; Ogbeche, Olofu Godwin (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
Since the second quarter of 2015, poverty levels in Nigeria have continued to rise, with existing palliative measures proving largely ineffective. This paper explores the multifaceted factors contributing to this trend, focusing particularly on the impact of changes in governance, economic policies, exchange rate volatility, and inflation on low-income earners and small to medium-scale entrepreneurs in Lafia, Nasarawa State. The study proposes a series of pragmatic strategies to mitigate the worsening socio-economic conditions faced by these groups. These include economic diversification into sectors such as agriculture, promotion of a savings culture, adoption of insurance policies, family planning, and encouraging spousal participation in small-scale enterprises such as retail businesses and vocational trades. The paper employs a qualitative research methodology, drawing on both primary and secondary data sources to offer a nuanced analysis of the current challenges and potential pathways for sustainable economic resilience.